StereoMorph: an R package for the collection of 3D landmarks and curves using a stereo camera set‐up. Issue 3 (2nd January 2015) - Olsen, Aaron M.; Westneat, Mark W.
Summary: Quantitative, three‐dimensional measurements of anatomy in biology and paleontology are key to understanding the evolutionary processes underlying morphological, functional and ecological diversification. However, the collection of 3D morphometric data from a large number of samples or in the field is currently limited by methods that are either too costly, too time‐consuming or lack portability. We present a new R package, StereoMorph, for the rapid and accurate collection of 3D landmarks and curves using two standard digital cameras. StereoMorph provides a complete set of tools for every step in the collection of 3D landmarks and curves using a stereo camera set‐up. This includes image processing and optimization functions for automated camera calibration using a checkerboard pattern, an easy‐to‐use application for digitizing landmarks and curves from photographs, and tools for reconstructing points and curves in 3D. The image processing tools and digitizing application are readily applicable to 2D morphometrics as well, enabling 2D landmarks and curves to be digitized and scaled automatically using a checkerboard pattern. We include five examples that demonstrate key functionalities of StereoMorph: automated detection of checkerboard corners, camera calibration, testing calibration accuracy, digitizing photographs and 3D curve reconstruction. With a set‐up costing less than 1500, we show that it is possible to achieve a mean reconstruction error of less than 30 microns. Once the cameras are assembled, specimens can be photographed as quickly as with 2D morphometrics while digitizing takes two to three times as long as digitizing a single photograph. We conclude by presenting an accompanying tutorial which details all of the steps required to collect 3D landmarks and curves using StereoMorph. Additionally, we present a web blog that will provide a platform for updates and user questions and suggestions.